A Concealed Claudian: The Meaning of 666 in Revelation - Nelson, Max ca. 20./21. Jh. (The journal of theological studies, 2025)
Various suggestions were made in Antiquity and the Middle Ages to explain the 666 of Revelation 13:18. Few of them are satisfactory, except perhaps for a neglected allusion to Sarapis, and the modern communis opinio is that it refers to Nero. After presenting an extensive survey and evaluation of previous guesses, I propose instead that 666 concerns an unknown heir to the imperial Claudian family, as the sum of the values of each letter in the name Κλαυδίας.